Islam and Mammon: The Economic Predicaments of Islamism - Timur Kuran (Princeton University Press, 2010)
IF ANGER, RESENTMENT, FRUSTRATION, AND ENVY were four of the factors that sowed the horrors of September 11, 2001, another is the belief that Islam offers solutions to entrenched problems of human civilization. Militants who strike in the name of Islamism, like millions of peaceful Islamists, argue, some no doubt with conviction, that Islam holds the key to a social order capable of providing social justice along with economic prosperity. Islam harbors an economic vision, Islamists contend, whose superiority has already been proven. Its first few decades in the seventh century, they say, and to an extent also the subsequent few centuries, amply demonstrate the merits of Islamic economic values and institutions. There exists a voluminous modern literature that purports to identify Islamâ€™s economic wisdom and to derive implications relevant to the present. Grounded in medieval Islamic thought, it is known as â€œIslamic economics.â€ Notwithstanding the claims of its promoters, the significance of this literature does not lie in its substance. It does not describe the advantages of Islamic economic principles in a manner that would make sense to a well-trained economist. Nor has it produced solutions that more than a small minority of Muslims take seriously. The significance of this literature lies chiefly in the support it gives to the quest for a distinctly Islamic social order. Islamic economics has fueled the illusion that Muslims can solve a wide range of social problems simply by embracing Islam and resisting Mammonâ€”the evils associated with immoral forms of economic gain. It has promoted the spread of antimodern, and in some respects deliberately anti-Western, currents of thought all across the Islamic world. It has also fostered an environment conducive to Islamist militancy. The most conspicuous assertion of Islamic economics is that interest is patently un-Islamic. Given the central role that interest plays in any modern economy, this claim sanctifies opposition to global economic integration. Most Muslims, whether or not they favor a ban on interest, and regardless of how they interpret Islam, readily agree that avoiding interest is among the constraints Islam places on economic behavior, if not its most important economic requirement. Likewise, non-Muslim observers of the Islamic world generally take it for granted that to shun interest is a basic Islamic requirement. Few people question whether the traditional sources of Islam do, in fact, prohibit all forms of interest. Nor is it common to encounter inquiries into whether the belief in a categorical ban has always enjoyed currency. Whatever their own attitudes toward interest, most observers, regardless of faith, believe that Islam treats interest as the clearest embodiment of Mammon. Among other doubtful assertions of Islamic economics is that Islam harbors an unsurpassed institution for redistributing wealth to the poor. And another is that the Islamic heritage offers economic norms well suited to ridding a modern economy of opportunism and corruption. Like the claim that Islam prohibits all interest, these assertions are rarely challenged explicitly or directly. Writings critical of Islamic economics, especially scholarly publications, are uncommon in any language.